84.8k views
3 votes
Please solve!
5x^3+3x−2x^3=3x^3

User Lubo
by
5.2k points

2 Answers

0 votes

Answer:0


Explanation:

5x^3+3x-2x^3=3x^3

collect like terms:

3x^3+3x=3x^3

cancel out equal terms on both sides:

3x^3+3x=3x^3

3x=0

divide both sides by 3

x=0

User Baby
by
5.3k points
4 votes

Answer:

x = 0

Explanation:

TO solve this, combine like terms.

3x^3 + 3x = 3x^3.

Then Subtract 3x^3 on both sides

3x = 0

Divide it all by 3.

x = 0

User Ahelm
by
6.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.